Economics as ideology : Keynes, Laski, Hayek, and the creation of contemporary politics - Hoover, Kenneth R., 1940- (Rowman & Littlefield, 2003)
Economics as Ideology explores the lives and thought of three powerful theorists who shaped the foundations of the center, left, and right of the political spectrum in the 20th century. Noted scholar Kenneth R. Hoover examines how each thinker developed their ideas, looks at why and how their views evolved into ideologies, and draws connections between these ideologies and our contemporary political situation.